A high-rate sodium dual-ion battery organic positive electrode material based on sulfur-enhanced n-pi conjugation and preparation and application thereof

CN122978397APending Publication Date: 2026-10-27UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610986033.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-27

Smart Images

  • Figure CN122978397A_ABST
    Figure CN122978397A_ABST
Patent Text Reader

Abstract

This invention discloses a high-rate organic cathode material for sodium dual-ion batteries based on the sulfur-enhanced n-π conjugation effect, its preparation, and its application, belonging to the field of electrochemical energy storage technology. The material is poly[10-methyl-3-(phenylazine-5(10H)-yl)-10H-phenthiazine](P(PhTz)), whose repeating unit is formed by C-N bond coupling of sulfur-containing phenthiazine units and dihydrophenthiazine units. This invention utilizes the n-π conjugation effect of the lone pair electrons of sulfur atoms and the aromatic π system to achieve global delocalization of the positive charge in the oxidation state, significantly reducing the HOMO energy level and accelerating the anion diffusion kinetics. This material exhibits an average discharge potential of 3.34 V and a discharge capacity of 185 mAh g⁻¹ in sodium half-cells. ‑1 It boasts a higher specific capacity and a groundbreaking 75C ultra-high rate performance; the assembled hard carbon anode full cell has an energy density of up to 536 Wh / kg. ‑1 Furthermore, it maintains excellent cycling stability at high rates. This invention solves the kinetic sluggishness caused by charge localization in traditional organic cathodes, providing a novel material solution for high-power sodium dual-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage and advanced organic synthetic materials technology, specifically relating to a nitrogen-rich conjugated polymer that utilizes a heteroatom electronic coupling mechanism to regulate charge distribution. More specifically, this invention discloses a high-performance p-type organic cathode material that significantly reduces the leading orbital energy level and accelerates ion diffusion kinetics by forming a strong n-π conjugation effect between the lone pair electrons of sulfur atoms and the aromatic π system, and its preparation and application in sodium dual-ion batteries. Background Technology

[0002] Sodium dual-ion batteries (SDIBs), as an emerging large-scale energy storage system, hold promise for overcoming the capacity bottleneck and improving energy density of traditional intercalation batteries due to their unique "cation-anion synergistic storage" mechanism—where cations intercalate into the negative electrode and anions intercalate into the positive electrode during charging. This is because the anion intercalation reaction typically occurs at a higher potential window (>3.0 V vs. Na). + SDIBs theoretically possess the potential for high voltage and high power output because they avoid the huge kinetic energy barrier caused by cation desolvation (Na) and cation desolvation.

[0003] However, the core challenge currently hindering the practical application of SDIBs lies in the difficulty of achieving both high operating voltage and high rate performance in cathode materials. While existing nitrogen-rich p-type organic cathodes (such as polytriphenylamine, polycarbazole, and dihydrophenazine derivatives) possess high oxidation potentials, their redox processes primarily rely on the gain and loss of electrons at the nitrogen atom centers. This localized charge storage mechanism leads to a high concentration of positive charges on the highly electronegative nitrogen atoms, causing severe electrostatic repulsion and structural polarization, resulting in multiple negative effects: on the one hand, localized charges hinder electron transport along the polymer backbone, leading to low intrinsic conductivity and sluggish kinetics; on the other hand, strong local electrostatic fields increase the activation energy for anion insertion, causing the material to fail under high current due to rapid polarization; furthermore, frequent volume changes and electrostatic stress can easily lead to polymer chain breakage or dissolution of active materials, severely shortening the battery's cycle life.

[0004] In existing technologies, although some studies have attempted to improve ion transport by introducing side-chain steric hindrance or constructing porous frameworks, these physical structural modifications have not addressed the fundamental defect of "charge localization" at the electronic level. Especially in scenarios requiring rapid charging and discharging (such as fast charging for electric vehicles and pulsed power supplies), the performance of conventional organic materials often drops drastically at rates exceeding 10C. Therefore, a novel design strategy is urgently needed to expand the delocalization range of π electrons at the molecular orbital level and achieve global charge dispersion, in order to achieve a breakthrough in both voltage and kinetic performance enhancement. Summary of the Invention

[0005] The purpose of this invention is to provide a high-rate organic cathode material for sodium dual-ion batteries based on the sulfur-enhanced n-π conjugation effect. By introducing a sulfur-containing heterocycle (phenothiazine unit), and utilizing the effective overlap between the unbonded lone pair electrons of sulfur atoms and the π orbitals of aromatic rings, a global n-π conjugated system is constructed. This strategy not only lowers the highest occupied molecular orbital (HOMO) energy level to increase the oxidation potential, but more importantly, it achieves a delocalized distribution of the positive charge in the oxidation state throughout the entire framework, thereby greatly reducing the anion insertion barrier and endowing the material with excellent high-rate performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: 1. An organic cathode material for high-rate sodium dual-ion batteries The material is poly[10-methyl-3-(phenylazine-5(10H)-yl)-10H-phenthiazine] (P(PhTz)). Its structural feature is that it is a conjugated polymer formed by alternating CN bonds between phenthiazine derivative units and dihydrophenthiazine derivative units. The sulfur atom in the phenthiazine unit acts as an electronic coupling hub, with its 3p orbital lone pair electrons participating in the full molecular π-conjugated system, forming a stable n-π interaction.

[0007] Preferably, the repeating unit structure is as follows:

[0008] Wherein, R is methyl or other short-chain alkyl; the linking bond is located at the 3 and 7 positions of phenothiazine and the corresponding active sites of dihydrophenothiazine.

[0009] 2. Preparation method of the above materials Includes the following steps: (1) Monomer mixing: Dissolve halophenothiazine monomers (such as 3,7-dibromo-10-methyl-10H-phenothiazine) and dihydrophenothiazine monomers in an anhydrous organic solvent; (2) Catalytic coupling: Palladium catalyst, phosphine ligand and base are added, and the mixture is heated under reflux under inert gas protection to carry out Buchwald-Hartwig coupling polymerization. (3) Post-processing: After the reaction is completed, precipitation, extraction and purification (to remove unreacted monomers, oligomers and metal residues) are performed, and vacuum drying is used to obtain the target polymer.

[0010] Preferred parameters: catalyst is Pd2(dba)3; ligand is XPhos or SPhos; base is NaOtBu; solvent is toluene or xylene; reaction temperature is 100-120°C, time is 24-72 hours.

[0011] 3. Application of the above materials in sodium dual-ion batteries It is used as a positive electrode active material in the assembly of sodium dual-ion full cells.

[0012] Preferably, the negative electrode is made of hard carbon (HC); the electrolyte is an organic solvent system containing a high-mobility anionic salt (such as NaClO4, NaPF6 or NaFSI); and the diaphragm is made of glass fiber or a commercial polyolefin diaphragm.

[0013] Compared with the prior art, the present invention has the following advantages: (1) Ultra-high rate performance: Unlike the diffusion control mechanism of traditional organic materials, P(PhTz) benefits from the charge delocalization and high-speed electron transport brought about by sulfur-enhanced n-π conjugation, and its electrochemical behavior is characterized by typical surface capacitance control. In half-cell tests, even at an extreme current density of 15 A / g (75C), it can still maintain about 60% of the capacity, which is far superior to the organic cathode materials reported in the existing literature (the performance usually decays significantly above 10C).

[0014] (2) High voltage plateau and high energy density: The introduction of sulfur atoms effectively lowered the HOMO energy level, increasing the average discharge potential to 3.34 V (vs. Na). + / Na). The full cell with a hard carbon anode has an energy density of up to 536 Wh kg⁻¹ (based on cathode mass), which is among the top levels of sodium dual-ion batteries.

[0015] (3) Structural stability and long-term cycling performance: The n-π conjugated system enhances intramolecular rigidity and interchain interactions, inhibiting structural degradation under oxidation. The full cell retains 71% of its capacity after 500 cycles at 1 A / g, and its performance remains stable under high-temperature loading conditions. Attached Figure Description

[0016] To clearly illustrate the technical solution of this invention, the accompanying drawings involved in this patent will be briefly described below. In the drawings: Figure 1 The synthetic route and monomer structure diagram of P(PhTz) are shown; Figure 2 The CV curve and constant current charge-discharge curve of P(PhTz) in a sodium half-cell are shown. Figure 3 Comparison of charge-discharge performance of P(PhTz) at different rates in sodium half-cells; Figure 4 The graph shows the cycling performance of P(PhTz) in a sodium half-cell. Figure 5 Charge-discharge curves and rate performance of HC||P(PhTz) full cells; Figure 6 The graph shows the cycle performance of an HC||P(PhTz) full cell. Detailed Implementation

[0017] The present invention will be further illustrated by specific embodiments below, but the scope of protection of the present invention is not limited thereto.

[0018] Example 1: Synthesis of poly[10-methyl-3-(phenylazine-5(10H)-yl)-10H-phenthiazine] (P(PhTz)) polymer In a nitrogen-protected glass tube reactor, 3,7-dibromo-10-methyl-10H-phenthiazide (738 mg, 2 mmol) and dihydrophenazine (DPZ, 364 mg, 2 mmol) were first added. Subsequently, RuPhos ligand (28 mg, 0.06 mmol), sodium tert-butoxide (692 mg, 7.2 mmol), and RuPhos Pd G2 catalyst precursor (46 mg, 0.06 mmol) were added sequentially. The reaction mixture was refluxed at 110°C with toluene (40 mL) as solvent and stirred for 72 hours. After the reaction was complete, the mixture was cooled to room temperature, and the solvent was removed by filtration. The resulting precipitate was washed with ethanol and deionized water to remove unreacted reagents and inorganic salt impurities. To further purify the target polymer, the crude solid was subjected to sequential Soxhlet extraction using dichloromethane, chloroform, and tetrahydrofuran to remove oligomers and low molecular weight impurities. Finally, the product was vacuum dried at 100°C for 8 hours to obtain a dark green solid P(PhTz) (724 mg, yield 93%).

[0019] Example 2: Electrode fabrication and sodium dual-ion full cell assembly Half-cell and positive electrode preparation: To prepare the P(PhTz) positive electrode, the P(PhTz) powder obtained in Example 1 was mixed with conductive Ketjen black and La133 aqueous binder in ethanol solvent. The mass ratio of active material, conductive agent and binder was set to 6:3:1 or 8:1:1. The uniformly ground slurry was coated onto an aluminum foil current collector and vacuum dried at 100°C for 8 hours to ensure complete solvent evaporation. Subsequently, the dried film was pressed into a circular electrode sheet with a diameter of 12 mm, and the active material loading was controlled at 2-3 mg / cm³. -2 The electrolyte system consisted of 1 M NaClO4 containing 5 wt% fluoroethylene carbonate (FEC) additive dissolved in a 1:1 volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC). A Whatman glass fiber membrane was used as the separator, and a sodium metal sheet was used as the counter / reference electrode. All CR2032 coin cells were assembled in an argon-filled glove box.

[0020] Full cell assembly: The sodium dual-ion full cell is assembled from a hard carbon (HC) anode and a P(PhTz) cathode. The HC anode slurry is prepared by mixing 80 wt% HC, 10 wt% SP conductive agent, and 10 wt% La133 binder, and coated onto copper foil with a loading of 5-6 mg cm⁻¹. -2 To suppress side reactions during the initial cycling period, the HC anode was pre-cycled twice in the range of 0.01–2.0 V, followed by discharge to 0.01 V. The pretreated anode was then removed in an argon glove box and used for full cell assembly. Furthermore, the mass ratio of P(PhTz) cathode to HC anode was set to approximately 1:2 (N / P ratio approximately 1.1–1.5) to promote charge transfer balance and maximize performance within an operating voltage range of 1.7–4.2 V.

[0021] Example 3: Electrochemical Performance Testing and Result Analysis Half-cell performance: like Figure 2-4 As shown, CV testing revealed three clear reversible redox peaks, corresponding to the DPZ, PTZ, and secondary oxidation of the DPZ unit. GCD testing indicated that at 0.1 A / g, P(PhTz) had an initial discharge capacity of 185 mAh / g and an average voltage of 3.34 V. Notably, when the current density was gradually increased to 15 A / g (75C), P(PhTz) still provided a reversible capacity of 107 mAh / g, and the curve plateau remained clear.

[0022] Full battery performance: like Figure 5-6 As shown, the HC||P(PhTz) full cell achieves an initial energy density of 536 Wh / kg at 0.1 A / g. In ultra-high rate testing, the full cell maintains effective capacity output at 75C, demonstrating excellent rate adaptability. Long-term cycling tests (1 A / g) show a capacity retention of 71% after 500 cycles, with a coulombic efficiency approaching 100%, demonstrating the stability of the sulfur-enhanced n-π conjugated structure during long-term cycling.

[0023] The above embodiments describe in detail the implementation of the present invention. Those skilled in the art can make conventional modifications and substitutions without departing from the concept of the present invention, and all such modifications should fall within the protection scope of the present invention.

Claims

1. A sodium dual-ion battery cathode material based on sulfur-enhanced n-π conjugation effect, characterized in that, The positive electrode material is poly[10-methyl-3-(phenylazine-5(10H)-yl)-10H-phenthiazine] (P(PhTz)); P(PhTz) is a copolymer formed by coupling phenthiazine derivative units and dihydrophenthiazine derivative units through CN bonds; wherein, the phenthiazine derivative units are selected from 10-substituted 3,7-dihalophenthiazine polymer structural segments, and the dihydrophenthiazine derivative units are selected from 5-substituted dihydrophenthiazine polymer structural segments; the general structural formula of P(PhTz) is as follows: Where R is methyl, ethyl or propyl.

2. A method for preparing poly[10-methyl-3-(phenylazine-5(10H)-yl)-10H-phenthiazine] as described in claim 1, characterized in that, Includes the following steps: Under an inert atmosphere, halophenothiazine monomers, dihydrophenothiazine monomers, palladium catalysts, ligands, and bases were mixed in an organic solvent and heated under reflux to carry out a Buchwald-Hartwig coupling reaction. After the reaction was completed, the crude product was collected by solid-liquid separation and purified by Soxhlet extraction using an organic solvent system with increasing polarity. The product was then dried under vacuum to obtain P(PhTz).

3. The preparation method according to claim 2, characterized in that, The halogenated phenothiazine monomer is 3,7-dibromo-10-methyl-10H-phenothiazine (MPTZ-2Br); the dihydrophenothiazine monomer is 5-phenyl-5,10-dihydrophenothiazine or 5,10-dihydrophenothiazine.

4. The preparation method according to claim 2, characterized in that, The palladium catalyst is selected from one or more of RuPhos Pd G2, Pd2(dba)3, and Pd(OAc)2; the ligand is selected from one or more of RuPhos, XPhos, SPhos, and P(t-Bu)3·HBF4; the base is selected from one or more of sodium tert-butoxide (t-BuONa) and cesium carbonate (Cs2CO3); and the organic solvent is selected from one or more of toluene, xylene, and N,N-dimethylformamide (DMF).

5. The preparation method according to claim 2, characterized in that, The reaction temperature is 100°C to 120°C, and the reaction time is 48 hours to 72 hours. The Soxhlet extraction solvent used in the purification step includes dichloromethane, chloroform, and tetrahydrofuran, which are extracted sequentially in order from nonpolar to polar to remove oligomers and impurities.

6. A sodium dual-ion full battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte; the positive electrode contains P (PhTz) as the active material as described in claim 1; the negative electrode is a hard carbon (HC) material; and the electrolyte is an organic electrolyte solution containing sodium salt.

7. The sodium dual-ion full battery according to claim 6, characterized in that, The positive electrode is composed of P (PhTz), a conductive agent, and a binder, with a mass ratio of 6:3:1 to 8:1:1; the conductive agent is selected from one or more of Ketjen Black (KB) and Super P; the binder is selected from one or more of polyvinylidene fluoride (PVDF), La133, and sodium carboxymethyl cellulose / styrene-butadiene rubber (CMC / SBR).

8. The sodium dual-ion full battery according to claim 6, characterized in that, The sodium salt in the electrolyte is sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), or sodium bis(trifluoromethanesulfonyl)imide (NaFSI); the solvent system contains at least two of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), and diethyl carbonate (DEC) in a volume ratio of 1:1 to 1:

2.

9. The sodium dual-ion full battery according to claim 6, characterized in that, The surface loading of the positive electrode active material is 2 mg cm⁻¹. -2 Up to 4 mg cm -2 The surface loading of the negative electrode active material is 5 mg cm⁻¹. -2 Up to 6 mg cm -2 The mass ratio (N / P ratio) of the positive electrode to the negative electrode is controlled between 1.1 and 1.

5.

10. A method for preparing a sodium dual-ion full cell as described in any one of claims 6-9, characterized in that, include: Preparation of positive electrode sheet: P(PhTz) active material, conductive agent and binder are mixed to form a slurry, which is coated on aluminum foil current collector, dried and rolled; Preparation of negative electrode sheet: Hard carbon material, conductive agent and binder are mixed to form a slurry, which is then coated onto copper foil current collector, dried and rolled. Pre-cycle treatment: The negative electrode sheet and the sodium metal counter electrode are assembled into a half cell and subjected to at least two charge-discharge cycles in the range of 0.01 V to 2.0 V to form a stable solid electrolyte interphase (SEI) film. Full cell assembly: The pretreated hard carbon anode is assembled with the P(PhTz) cathode, along with a separator and electrolyte, into a full cell.